2021
DOI: 10.3390/healthcare9020205
|View full text |Cite
|
Sign up to set email alerts
|

Communication on Safe Caregiving between Community Nurse Case Managers and Family Caregivers

Abstract: Dependent elderly individuals are usually cared for at home by untrained family members who are unaware of the risks involved. In this setting, communication on safe caregiving is key. The aim of this study is to describe the factors influencing the process followed by community nurse case managers to provide communication on safe caregiving to family members caring for dependent elderly individuals. A phenomenological study, by focus group, was done in urban healthcare facilities. Key informants were seven co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…It is noteworthy that all the healthcare professionals participating in our study highlighted the case management nurse as a key element for medication reconciliation, which is in line with other studies [28]. The main function of case management nurses is ensuring precise coordination and communication between the different levels of care [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is noteworthy that all the healthcare professionals participating in our study highlighted the case management nurse as a key element for medication reconciliation, which is in line with other studies [28]. The main function of case management nurses is ensuring precise coordination and communication between the different levels of care [22].…”
Section: Discussionsupporting
confidence: 85%
“…Poor multidisciplinary communication with the hospital and fragmented communication between levels of care lead to chaotic and non-systematic transitions [21,26]. The need to improve communication between healthcare professionals and patients and their informal caregivers has been shown to ensure proper medication reconciliation [11,22,27,28]. Taking such facts into account, the WHO has stated that good communication is vital for successful medication reconciliation, so it proposed to create and implement a specific communication strategy for it [1].…”
Section: Introductionmentioning
confidence: 99%
“…Case managers and nurses know the dual yet separate health care roles of FHH and FMH. They would be viable gatekeepers to model and educate patients, their health proxies, and other health care professionals on FHH and FMH utilization (Gursansky et al, 2020; Macías-Colorado et al, 2021). Therefore, homogenizing FHH and FMH among patients, families, case managers, and nurses will complement personalized health care through direct contact or web-based platforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond the health-care team, NCM highlight the relevance of context to the care of EAR. In this sense, the study conducted by Macias-Colorado et al [ 60 ] highlights how case managers considered factors related to the patient’s environment and primary caregiver to be crucial to the patient’s safety, highlighting three of these factors: (1) the need for the caregiver to accept and assume her role, (2) recognition of her work by other family members and, consequently, to help her in her rest and self-care, and (3) an adequate economic situation. These authors do not mention the problems of accessibility and barriers in housing, as different studies [ 61 , 62 ] have reported and as described in the results of our study.…”
Section: Discussionmentioning
confidence: 99%